THE PROBLEM OF CONSTITUTIONALISM OF VILLAGE HEAD TENURE IN THE DIMENSION OF THE STATE OF LAW AND DEMOCRACY - Muchlisin Alfarabi (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
The research in this journal is entitled